Kerja Sama Kantor Detensi Imigrasi dan International Organization For Migration: Studi Kasus Perlindungan Pengungsi dan Pencari Suaka Anak di Rumah Detensi Imigrasi Semarang - Teu Meryesca Wicaksari; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Refugees and asylum seekers stationed in Semarang detention center form afamily group that cause many children there. In an effort to protect refugeesand child asylum seekers, the Semarang immigration detention center incollaboration with the International Organization for Migration in handlingthe needs during the process of determining the status of the United NationHigh Commissioner for Refugees in Semarang rudenim. The purpose of thisresearch is to explain the cooperation used to protect the right of refugees andasylum seekers in rudiment in Semarang. Policies on the fulfillment of theright to live (to obtain food), health and education are central to the policiesadopted in Semarang Rudenim Using the concept of policy implementation,this study argues that interagency cooperation is essential to implementpolicy strategies. The results of this study indicate that cooperative efforts ofrefugee protection and child asylum seekers are done by fulfilling the basicrights of children in accordance with the Universal Declaration of HumanRights. This cooperation involves the Regional Government of SemarangCity and child-observer NGOs in Semarang City.